Collaborative Governance for Social Protection Policy in Karimun Regency - Syarifah Rina Elva; Rumzi Samin; Fitri Kurnianingsih (Syntax Corporation Indonesia, 2023)
The aim of the Collaborative Governance research in social protection policy in Karimun Regency is to explore and analyze the process and dynamics of collaboration among various parties in implementing social protection policy in Karimun Regency, as well as to evaluate the effectiveness and efficiency of applying Collaborative Governance in social protection policy. Qualitative research method is employed in studying Collaborative Governance in social protection policy by Karimun Regency, which can be carried out in several stages. The purpose is to understand how the collaboration process between various stakeholders takes place in developing social protection policy. The results show that based on the concept of collaboration in Collaborative Governance, we can imagine that social protection policy in Karimun Regency involves the participation of various related parties, such as government agencies, communities, NGOs, and private sectors. This collaboration aims to achieve better outcomes in social protection in Karimun Regency by applying participatory, inclusive, and transparent principles. Therefore, Collaborative Governance is likely to improve the effectiveness of social protection policy in Karimun Regency through collaborative processes and outcomes between involved parties in the policy. Through this approach, various parties can share information, resources, and responsibilities in formulating and implementing policies. In the context of social protection policy in Karimun Regency, Collaborative Governance can facilitate discussion and cooperation among local government, civil society organizations, and society as the target of the policy.